Utilization of recycled glass for 3D concrete printing : rheological and mechanical properties - Ting, Andrew Guan Heng (2020)
The disposal of post-consumer glass has been a major issue due to its inert properties that may cause environmental effects, while recycling of these glasses is only feasible if the waste glass recovered is sorted into its different colour to prevent chemical incompatibility in the manufacturing process. 3D printing in building and construction has gain increasing attention in the past decade and provides a potential to sustainably utilize the recycled unsorted glasses. This paper examines the use of recycled glass as the fine aggregates for 3D concrete printing applications. Despite the several studies done on the use of recycled glass in concrete, there is a lack of focus on the rheology of the material which is essential to the performance of the material in 3D concrete printing. Although results have shown that the mechanical strength for the recycled glass concrete is lower than the sand aggregates concrete, yet the flow properties of the former is better than the latter. Nonetheless, a balance between the mechanical strength and flowability of the mix design should be studied. The future work revolves around the optimization of the mix design using a combination of sand and recycled glass, adjusting the gradation of recycled glass particles and addition of accelerators to improve its buildability and mechanical strengths.